Engaged pedagogies in the middle grades: A case study of justice-oriented teachers in COVID times - Hilary E Hughes; Rachel Ranschaert; Kelsey L Benson (Middle Grades Review, 2023)
Much of the extant literature regarding middle grades teachers centers on interventions to improve the quality or effectiveness of their teaching: studies that identify a particular instructional strategy, curricular support, or disposition, and conclude with recommendations that teachers improve their practice by adopting said thing. In contrast, the qualitative case study we present here contributes to the rising tide of research illustrating the powerful, transformative work that middle grades teachers oriented toward justice and equity are already doing in the classroom. Specifically, we draw on eight months of data to illuminate how teachers in a Title I middle school located in the southeastern United States enacted what bell hooks (1994) refers to as engaged pedagogy. By this, we mean educators who believe we learn best when there is an interactive relationship between teachers and students; are continuously engaging in self-actualization by working to identify and unlearn harmful, dominant narratives about race/ethnicity, social class, dis/ability, and gender; and who attend to their own well-being so they can better attend to their students’ overall academic and social-emotional well-being. Rather than a blueprint assumed to be generalizable, we offer these illustrations to underscore the importance of developing and supporting justice-oriented middle grades teachers who are and/or will become engaged pedagogical practitioners.
Keywords: middle level teaching; middle grades teaching; social justice teaching; engaged pedagogy